Business Process Improvement in Call Center Operations at XYZ Malaysia Using Lean Six Sigma - Andini, Trisnawati; Yudoko, Gatot (Jurnal Bisnis dan Pemasaran Digital, 2024)
Purpose: This study explores the application of Lean Six Sigma methodologies to improve the business process in call center operations at XYZ Malaysia to enhance service quality and increase customer satisfaction. This study emphasizes the importance of adopting Lean Six Sigma. Research Methodology: This study employed a mixed-method approach that utilized both qualitative and quantitative data. Qualitative data explores challenges and customer satisfaction levels, while quantitative data assesses the impact of Lean Six Sigma on specific metrics used by the call center. Results: The findings suggest that Lean Six Sigma methodologies can provide a structured approach to problem-solving and process enhancement, enabling call centers to achieve higher performance standards. The findings underscore the potential of Lean Six Sigma to drive continuous improvement, ensuring that call center operations not only meet but also exceed customer expectations. Ultimately, this approach is expected to set new standards for customer care and call center management, particularly in the English-speaking market, contributing to XYZ Malaysia's vision of delivering outstanding customer experiences through exceptional service quality. Conclusions: The study concludes that XYZ Malaysia's call center operations have significant potential to improve performance by focusing on Average Handling Time (AHT), Customer Satisfaction Scores (CSAT), and Resolution Rates (RR) using Lean Six Sigma's DMAIC framework. Limitations: This study is limited to data from Q1–Q2 2024 and focuses primarily on three key performance indicators without deeper analysis of workforce behavior, system constraints, or customer demographics. Contributions: This research demonstrates how applying Lean Six Sigma and process capability analysis can identify inefficiencies and guide strategic improvements in a call center environment.